2015
DOI: 10.1016/j.arthro.2015.04.027
|View full text |Cite
|
Sign up to set email alerts
|

Medial Quadriceps Tendon-Femoral Ligament (MQTFL) Reconstruction for Patellofemoral Instability

Abstract: were included. 28/38 (74%) successfully completed non-op treatment whereas 10/38 (26%) failed after a median of 44 days (range, 6-511) from the initiation of physical therapy. Of the 10 patients who failed, 9 (90%) sought treatment >30 days after the injury. Two of these patients had a subsequent surgery before final follow-up and were therefore not included in outcomes analysis. Follow-up was available for the remaining 7/8 patients (87.5%) who failed non-op treatment and for 22/28 patients (78%) who were suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…14,[23][24][25][26] Anatomic reconstruction of the MQTFL with either the Fulkerson method or our sling variation also avoids transosseous fixation and has obtained excellent subjective and objective results at short-term follow-up. The only other report of this technique is by Fulkerson and Edgar, 1 with their follow-up as reported by Barden et al 17 In their original description of the technique, Fulkerson and Edgar reported 1-year follow-up of 17 patients who had MQTFL reconstruction; none had a recurrence of patellar instability. The later report by Barden and colleagues described a 3-year follow-up of 28 patients (29 knees) with MQTFL reconstruction, none of whom experienced a complete dislocation, 26 (93%) of the 28 patients were satisfied with their surgical outcomes, and 25 (89%) were able to return to the same or higher level of activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…14,[23][24][25][26] Anatomic reconstruction of the MQTFL with either the Fulkerson method or our sling variation also avoids transosseous fixation and has obtained excellent subjective and objective results at short-term follow-up. The only other report of this technique is by Fulkerson and Edgar, 1 with their follow-up as reported by Barden et al 17 In their original description of the technique, Fulkerson and Edgar reported 1-year follow-up of 17 patients who had MQTFL reconstruction; none had a recurrence of patellar instability. The later report by Barden and colleagues described a 3-year follow-up of 28 patients (29 knees) with MQTFL reconstruction, none of whom experienced a complete dislocation, 26 (93%) of the 28 patients were satisfied with their surgical outcomes, and 25 (89%) were able to return to the same or higher level of activity.…”
Section: Discussionmentioning
confidence: 99%
“…Their cohort experienced a high-rate of return to sport (89%) and no recurrent dislocations, but apparently, 3 patients did have some remaining instability. 1,17 In their technique, the graft is sutured into the distal quadriceps tendon. We describe a modification of this technique, in which a sling is created in the distal quadriceps tendon, the graft is doubled back, and both ends are fixed at the femoral isometric point.…”
mentioning
confidence: 99%
See 1 more Smart Citation